2003
DOI: 10.1038/nm884
|View full text |Cite
|
Sign up to set email alerts
|

Role of PlGF in the intra- and intermolecular cross talk between the VEGF receptors Flt1 and Flk1

Abstract: Therapeutic angiogenesis is likely to require the administration of factors that complement each other. Activation of the receptor tyrosine kinase (RTK) Flk1 by vascular endothelial growth factor (VEGF) is crucial, but molecular interactions of other factors with VEGF and Flk1 have been studied to a limited extent. Here we report that placental growth factor (PGF, also known as PlGF) regulates inter- and intramolecular cross talk between the VEGF RTKs Flt1 and Flk1. Activation of Flt1 by PGF resulted in interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
574
2
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 682 publications
(610 citation statements)
references
References 44 publications
22
574
2
6
Order By: Relevance
“…It can also form a heterodimer with PlGF, and this stimulates angiogenesis via the VEGFR-1/VEGFR-2 heterodimer (Autiero et al, 2003;Roy et al, 2006); this is consistent with our finding that VEGF/PlGF was present at substantially higher levels in AML patients than in the healthy controls. Loges et al (2005) reported that the AML patients and healthy donors …”
Section: Discussionsupporting
confidence: 92%
“…It can also form a heterodimer with PlGF, and this stimulates angiogenesis via the VEGFR-1/VEGFR-2 heterodimer (Autiero et al, 2003;Roy et al, 2006); this is consistent with our finding that VEGF/PlGF was present at substantially higher levels in AML patients than in the healthy controls. Loges et al (2005) reported that the AML patients and healthy donors …”
Section: Discussionsupporting
confidence: 92%
“…In the vascular endothelium, VEGF increases paracellular permeability by the activation of VEGF-R2 receptors (Autiero et al 2003;Gille et al 2001;Shen et al 1999). However, a recent study by Miyamoto and colleagues concluded that the VEGF-R1 receptor subtype mediated VEGF-induced changes in the barrier properties of ARPE-19 cell monolayers (Miyamoto et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to begin to understand how VEGF contributes to the regulation of RPE barrier function, it is essential to understand how individual VEGF receptors effect RPE physiology. In vascular endothelial cells, there is growing evidence that increases in permeability and proliferation are mediated by VEGF-R2 activation, and within the choroid, that these actions can be opposed by VEGF-R1 stimulation (Autiero et al 2003;Gille et al 2001;Nozaki et al 2006;Shen et al 1999). However, a recent study of the RPE concluded that VEGF-R1 receptor activation is responsible for the VEGF-induced increase in epithelial permeability (Miyamoto et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Like most solid tumors, gliomas express and secrete vascular endothelial growth factor/vascular permeability factor (VEGF/VPF) that induces proliferation and migration of neighboring endothelial cells [32][33][34][35][36]. Remodeling of the BBB vasculature by VEGF disrupts the formation of tight junctions, increases vascular permeability (VP), and results in a disordered vasculature characteristic of tumor-induced angiogenesis [34,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%